Comparative Efficacy of Plant Leaves in Remediation of Crude Oil Polluted Silty Soil - Nnadikwe Johnson; Otaraku, Ipeghan Jonathan; Oji Akuma; Samuel Nwaozuzu (Journal Majelis Paspama, 2026)
This study compared the efficacy of Jatropha curcas and Vernonia amygdalina leaf extracts in bioremediating crude oil-polluted silty soil through composite bioaugmentation. Wet-blended extracts (with P. aeruginosa, S. aureus, E. coli) achieved >50% contaminant reduction in 40 days. Predictive models (Minitab) explained remediation outcomes, highlighting the potential of these plant extracts as eco-friendly agents for silty soil restoration in Ogoniland, Niger Delta, Nigeria. The study investigated the comparative efficacy of Jatropha curcas and Vernonia amygdalina leaf extracts in bioremediating crude oil-polluted soils through composite bioaugmentation. The leaf extracts, harboring P. aeruginosa, S. aureus, and E. coli, were prepared via sun drying, room drying, and wet blending, and applied to contaminated sandy, loamy, and silt soils. Results showed that wet-blended extracts demonstrated superior remediation performance, achieving over 50% reduction in contaminant levels. Treatment with 10-40g of leaf extract over 40 days significantly reduced contaminants, with optimal results observed in sandy soils. Using Minitab software, predictive models were developed to estimate the impact of leaf mass, treatment time, and soil pH on the remediation of hydrocarbons, lead, zinc, and chromium. The models were statistically significant (p < 0.05) with good explanatory power (high R²), indicating their potential for predicting remediation outcomes. These findings highlight the potential of Jatropha curcas and Vernonia amygdalina as effective bio-remediation agents for crude oil-polluted soils, offering a sustainable solution for environmental restoration.